2022
DOI: 10.22365/jpsych.2022.057
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacology of patients with multiple sclerosis in Greece during the period 2017-2019

Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive method of brain stimulation that is receiving increasingly attention for new clinical applications. Through electromagnetic induction cortical activity can be modulated and therapeutic effects can be achieved in a variety of psychiatric and neurological conditions. According to the World Health Organization (WHO) depression is the most disabling disease in the world and 350 million people suffer from depression globally. Major depression is the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Given the prevalence of depressive and anxiety disorders in the course of MS, it seems reasonable to consider the administration of selective serotonin reuptake inhibitors (SSRIs) in these patients. It was shown that, due to the improvement in mental status, appropriate monitoring but also adequate treatment of psychiatric symptoms can improve the long-term prognosis of the disease [ 65 ]. Moreover, studies are underway on the effect of SSRIs on the pathogenesis of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of depressive and anxiety disorders in the course of MS, it seems reasonable to consider the administration of selective serotonin reuptake inhibitors (SSRIs) in these patients. It was shown that, due to the improvement in mental status, appropriate monitoring but also adequate treatment of psychiatric symptoms can improve the long-term prognosis of the disease [ 65 ]. Moreover, studies are underway on the effect of SSRIs on the pathogenesis of MS.…”
Section: Discussionmentioning
confidence: 99%